The Peak of Prophetic Civilization in The Time of The Rasulullah Saw - Aditia, Wahyu; Damsir , Muhammad (Khulasah : Islamic Studies Journal, 2025)
A very honest confession from Michael H. Hart in his book entitled « The 100 : A Ranking Of The Most Influential Person in History” in this book he places the Prophet Muhammad SAW as the most influential human history. That is the truth, for us as Muslims we definitely believe that in a religious context the Prophet Muhammad was a very influential figure and had a very big name that could not be rivaled by anyone from various sectors. So on this occasion we try to describe how the peak of prophetic civilization was, especially during the time of the Prophet Muhammad SAW, at that time there was often a connection between heaven and earth through him, the idealism of all events also occurred on earth and it was at that time that the peak of prophetic civilization occurred. In this paper we use the library research method, and through descriptive-analytical analysis from several reference sources in this paper we will show the condition of Arab society before the arrival of Islam, then in the Mecca period, and in the Medina period. In the end, we can find that in that period there was the best period, the most ideal period, and the peak of prophetic civilization, so that in the future it would become an example for humans to achieve a good, prosperous and safe social life accompanied by faith in Allah SWT.